Towards a Standardized User Model for Personalized Systems in Health - Rico Olarte, Carolina; Giron Buitron, Edwar Javier; Ceron Rios, Gineth Magaly; Lopez Gutierrez, Diego Mauricio (Sistemas y Telemática, 2015)
The definition of a user model supports personalization in computer-based systems. For a personalized system in health, which supports the promotion of healthy habits and lifestyles, in particular physical activity and healthy diet, a user model according to the ISO/TR 14292 standard for Personal Health Records [PHR] is proposed. The description of the standardized user model includes: a characterization of the user model; the proposed user model according to the ISO standard; the relationships and inferences of the user model; and reference architecture for the system to be developed. Finally, a prototype with a small dataset is implemented and some possible mockups supporting the proposed architecture are designed.
Created from Fastlane, WoS look-up